Integration of AI with reduced order generalized integrator controller for power system harmonic reduction. (12th May 2020) - Mandava, Srihari; Medarametla, Praveen Kumar; Gudipalli, Abhishek; Saravanan, M; Sudheer, P
Abstract: The increased use of electronics for control and use of nonlinear type loads by consumers in the present power system network are injecting harmonics into the power signal, due to which the power quality issue has become more challenge for the present researchers. In this work, the reduced order generalized integrator (ROGI) and fuzzy logic control (FLC) are collectively used to reduce the current harmonics in the power system. FLC‐SVM technique is used to maintain the process of SAF—Shunt active filter with fixed switching frequency. This proposed control technique consists of control loop for current to have fast and effective control. The Proportional Resonant controller is used to have control on voltage for a slow and effective control process which is also used to compensate reactive power. The shunt active filter is designed with the help of ROGI by integrating PI controller for fuzzy‐based SVM to reduce the current harmonics on the load side. The results are achieved in MATLAB/SIMULINK software.